Vitamin D downregulates key genes of diabetes complications in cardiomyocyte. Issue 11 (7th June 2019) - Derakhshanian, Hoda; Djazayery, Abolghassem; Javanbakht, Mohammad Hassan; Eshraghian, Mohammad Reza; Mirshafiey, Abbas; Jahanabadi, Samane; Ghadbeigi, Sajad; Zarei, Mahnaz; Alvandi, Ehsan; Djalali, Mahmoud
Abstract: Objective: Vitamin D deficiency has been reported to be associated with the incidence of type 1 and type 2 diabetes and worsening of diabetes complications. This study was designed to investigate the effect of vitamin D treatment on the expression of five key genes involved in the development of diabetic cardiomyopathy. Methods: Twenty‐four male Sprague–Dawley rats were randomly divided into three groups. The first group served as control and the other two groups received an intraperitoneal injection of 45 mg/kg streptozotocin (STZ) to develop diabetes. Then groups were treated for 4 weeks either with placebo or vitamin D (two injections of 20, 000 IU/kg). Serum levels of glucose, insulin, HbA1c, and advanced glycation end products (AGEs), as well as the gene expression of AGE cellular receptor (RAGE), glyoxalase, aldose reductase, O‐GlcNAc transferase (OGT), and glutamine‐fructose‐6‐phosphate aminotransferase (GFAT) and nuclear factor‐kB (NF‐kB) activity of nuclear extracts were assessed at the end of experiment. Results: Increment in serum cholecalciferol could improve hyperglycaemia and hypoinsulinemia in diabetic rats. In addition, a significant reduction was observed in RAGE, OGT, and GFAT gene expression and NF‐kB activity in cardiac myocytes. Conclusions: Vitamin D might contribute in reducing diabetic cardiomyopathy not only by improving blood glucose and insulin levels but also via downregulating AGE and hexosamine pathways and decreasing NF‐kB activity in heart tissue. Abstract : Vitamin D may ameliorate cardiac complications of diabetes by suppressing hexosamine and advanced glycation end‐products pathways.